Vitamin K1 levels in the umbilical cord blood of neonates in Arkhangelsk - L. G. Kiseleva; G. N. Chumakova; A. G. Soloviev; O. A. Kharkova; D. S. Kosyakov; N. V. Ulyanovsky; E. M. Gryzunova; Л. Г. Киселева; Г. Н. Чумакова; А. Г. Соловьев; О. А. Харькова; Д. С. Косяков; et al. (Rossiyskiy Vestnik Perinatologii i Pediatrii (Russian Bulletin of Perinatology and Pediatrics), 2017)
The optimal course of biochemical processes needs adequate dietary intake of vitamins involved in the body’s metabolic reactions. The basis for the pathogenesis of neonatal hemorrhagic disease is deficiency of vitamin K, the level of which in the North-Western Region of Russia was estimated for the first time.Objective: to measure umbilical cord blood vitamin K1 levels in newborn infants.Methods. Forty full-term newborns were examined. Vitamin K1 levels were determined using high performance liquid chromatography-tandem mass spectrometry.Results. The mean umbilical blood cord level of vitamin K1 was very low and amounted to 0.05 (<0.03; 0.15) µg/l. This study revealed no relationship between the level of the above trace element and neonatal sex (p=0,854), maternal age (p=0,913), abortions (p=0,568), threatened abortion (p=0,109), smoking (p=0,923).Conclusion. The umbilical cord blood concentration of vitamin K1 in the newborns was found to be very low, which increases the risk of hemorrhagic disease and requires exogenous replenishment of the above vitamin after birth. Для оптимального течения биохимических процессов необходимо адекватное поступление витаминов, участвующих в метаболических реакциях организма. В основе патогенеза геморрагической болезни новорожденных лежит дефицит витамина К, оценка содержания которого в условиях Северо-Западного региона России проводилась впервые.Цель: определить содержание витамина К1 в пуповинной крови новорожденных.Методы. Обследованы 40 доношенных новорожденных. Определение витамина К1 осуществлялось методом высокоэффективной жидкостной хроматографии/тандемной масс-спектрометрии.Результаты. Средний уровень витамина К1 в пуповинной крови оказался очень низким и составил 0,05 (<0,03; 0,15) мкг/л. Не отмечено взаимосвязи между уровнем указанного микроэлемента и полом новорожденных (р=0,854), возраста матерей (р=0,913), наличием абортов (р=0,568), угрозы прерывания беременности (р=0,109), табакокурения (р=0,923).Вывод. Выявлена очень низкая концентрация витамина К1 в ...